2001
DOI: 10.1258/1357633011936507
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of teleconsultations versus face-to-face consultations

Abstract: We compared the diagnoses made by one dermatologist via telemedicine with those of another dermatologist made in a face-to-face consultation. The patients first underwent a teledermatology consultation and then a face-to-face consultation. A general practitioner was present with the patient in the videoconference studio. Videoconferencing equipment connected at 384 kbit/s was used. The doctor-patient relationship and the satisfaction of the patients and dermatologists in the two settings were assessed, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 27 publications
1
69
1
3
Order By: Relevance
“…Several studies showing the feasibility and usefulness of e-visits in dermatology have already been described in the literature, and a high accordance for diagnosis between live visits and e-consultations has been reported in all of them [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. Most of these studies demonstrate high accordance for the diagnosis of inflammatory and neoplastic skin diseases [17, 18, 19, 20, 21], and particularly for the diagnosis of pigmented skin lesions (teledermoscopy) [22, 23, 24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showing the feasibility and usefulness of e-visits in dermatology have already been described in the literature, and a high accordance for diagnosis between live visits and e-consultations has been reported in all of them [2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16]. Most of these studies demonstrate high accordance for the diagnosis of inflammatory and neoplastic skin diseases [17, 18, 19, 20, 21], and particularly for the diagnosis of pigmented skin lesions (teledermoscopy) [22, 23, 24, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Baumeister et al [12] tested and compared two validated scores (Osnabrück Hand Eczema Severity Index; Hand Eczema Severity Index) for their suitability in an occupational telemedical screening and showed that both scores were suitable to asses severity of hand eczema by teledermatology. Nordal et al [13 ]compared the diagnoses made by one dermatologist via telemedicine with those of another dermatologist made in face-to-face consultation. Of 121 patients, there was a high degree of concordance between the two sets of diagnoses, with 72% complete agreement and 14% partial agreement between the two dermatologists [13].…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study also found no differences in diagnostic accuracy with a compression factor of 30 but determined the reproducibility of diagnostic judgment was greater with images uncompressed. 9 Fourteen percent of diagnoses were adversely affected by picture quality in a videoconferencing study, 10 whereas other studies indicate video quality may be inadequate for some exams 11 and inferior to still images. 12 Several studies have suggested there may be a minimal compression and transmission threshold.…”
Section: Compressed Videomentioning
confidence: 93%